2003
DOI: 10.1038/nmat854
|View full text |Cite
|
Sign up to set email alerts
|

Slippery questions about complex fluids flowing past solids

Abstract: Viscous flow is familiar and useful, yet the underlying physics is surprisingly subtle and complex. Recent experiments and simulations show that the textbook assumption of 'no slip at the boundary' can fail greatly when walls are sufficiently smooth. The reasons for this seem to involve materials chemistry interactions that can be controlled--especially wettability and the presence of trace impurities, even of dissolved gases. To discover what boundary condition is appropriate for solving continuum equations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
336
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(353 citation statements)
references
References 47 publications
6
336
2
2
Order By: Relevance
“…It is reported in sedimentation studies [16] that slip was not observed in vacuum conditions but only when the liquid sample was in contact with air. Furthermore, the study in [63] showed that tetradecane saturated with CO 2 lead to results consistent with no-slip but significant slip when saturated with argon, whereas the opposite behavior was observed for water. Similar results were reported in [161].…”
Section: Dissolved Gas and Bubblesmentioning
confidence: 93%
“…It is reported in sedimentation studies [16] that slip was not observed in vacuum conditions but only when the liquid sample was in contact with air. Furthermore, the study in [63] showed that tetradecane saturated with CO 2 lead to results consistent with no-slip but significant slip when saturated with argon, whereas the opposite behavior was observed for water. Similar results were reported in [161].…”
Section: Dissolved Gas and Bubblesmentioning
confidence: 93%
“…A number of new studies have confirmed the existence of a liquid slip over certain solid surfaces, as summarized in recent reviews. [5][6][7] Although a few studies 8,9 have reported a slip over hydrophilic surfaces, many theoretical, 10,11 experimental, [12][13][14][15][16][17][18][19][20][21][22][23] and numerical 24 studies have reported that hydrophobic surfaces allow a noticeable slip ranging from nanometers to a micron in "slip length" ͑the linearly extrapolated distance into a solid surface at which a no-slip condition would hold true͒. Several reasons have been proposed for the slip over hydrophobic surfaces, including a molecular slip, 10 a decrease in the viscosity of the boundary layer, 11 the small dipole moment of a polar liquid, 23 and a gas gap or nanobubbles at the liquid-surface interface.…”
Section: Introductionmentioning
confidence: 99%
“…Such an apparent slip introduces a larger velocity difference at the boundary while the fluid speed seems (but in fact does not) to extrapolate to zero below the surface (Granick et al, 2004;Forster and Smith, 2010). In this model, an apparent slip is enabled when adding the boundary condition "wetted wall".…”
Section: Model Domains and Initial Model Set-upmentioning
confidence: 99%